Online product selection system of REH Trading - Ang, Tzy Guan (2012)
Online Product Selection System of REH Trading (OPSS) is a web-based system that helps REH Trading to manage their business online and allow customer to make order and view support.The existing system of the company does not optimize the usage of internet services.The system just provides simple company profile,product view and contact of the company.There is no guide service for customer to choose the right product.Therefore,this system is developed to manage the company business and provide product selection service by using rule-based forward chaining.There are two targeted users in this system, which are the admin staff and the customers of REH Trading.The modules of the system are login and registration,view product,view support,make appointment and order,manage order and profile,search product and approve order and appointment.Rapid Application Development (RAD) model is used to develop this project.There are four phases which are requirements planning,user design, construction and cutover.The testing results shown that the proposed system gives user flexibility to choose the product smartly.